KEANEKARAGAMAN FUNGI MIKORIZA ARBUSKULA DI HUTAN DATARAN RENDAH DAN HUTAN PANTAI PULAU NUSAKAMBANGAN TIMUR - Fadilah Yudi Arkhami; Sri Wilarso Budi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2026)
Arbuscular mycorrhizae represent a form of mutualistic symbiosis between fungi and plant roots. The fungi obtain carbohydrates and energy from the plants, while the plants benefit from nutrients, hormone and water supplied by the fungi. This study aimed to: (1) to compare the diversity of spores, spore density, relative frequency, relative abundance, and colonization of arbuscular mycorrhizal fungi (AMF) in lowland forests ecosystem and coastal forests ecosystem, and (2) analyze the relationship between spore density and AMF colonization. Soil and root sampling was carried out in three plots within each forest ecosystem. The results showed that the diversity of AMF genera was higher in lowland forests ecosystem than in coastal forests ecosystem. The identified AMF genera included Glomus, Acaulospora, Gigaspora, Scutellospora, Sclerocystis, Diversispora, and Entrophospora, with Glomus and Acaulospora being the dominant genera in both forest ecosystem. The spore density and root colonization of AMF in the lowland forest and coastal forest did not differ significantly. Spore density and root colonization of AMF were higher in coastal forests ecosystem. A positive correlation was found between spore density and AMF colonization in both ecosystem forest.